Human embryo: what about relatedness? - Terranova, Corrado; Angioli, Roberto; Feole, Laura; Plotti, Francesco; Fais, Giuseppina; Rampello, Stefania; Campanozzi, Laura; Ricci, Giovanna; Ghilardi, Giampaolo; Tambone, Vittoradolfo (Medicina e Morale, 2020)
Many studies are still ongoing to allow a global comprehension of the complex mechanisms that characterize and regulate human embryo development during the first weeks of his life. In this article, we decided to explore in particular one aspect of human embryo development: relatedness. Using PubMed database, we selected articles related to this particular theme and 56 articles where included in our analysis. We considered three different types of relatedness: from embryo to mother, from mother to embryo and bilateral relatedness. For each article, we indicated what type of relatedness was mainly present either during pre-implantation phase or during implantation phase or during post-implantation phase. The complex interactions between the mother and the embryo have been discussed and represented using, as emerged from literature, a cooperative agents' model.